Live Streaming Strategies and Time Pressure: Their Effect on Perceived Urgency and Impulse Buying Behavior on Shopee - Zakiah, Nawal Noor (Fakultas Ekonomi Universitas Garut, 2025)
The study aims to examine the effect of live streaming on perceived urgency and impulse buying, as well as the role of time pressure as a moderating variable in Shopee's e-commerce marketing context. Additionally, the study investigates how time pressure enhances the relationship between perceived urgency and impulse buying behavior. Data were collected from 240 respondents, consisting of Generation Z and millennial consumers. The data analysis was conducted using the Structural Equation Modeling (SEM) method with AMOS version 22 software. The results show that live streaming significantly influences perceived urgency, which in turn positively impacts impulse buying behavior. Time pressure was also found to strengthen the relationship between live streaming and perceived urgency, as well as between perceived urgency and impulse buying.